Nutritional interactions in the Peruvian daily diet and their impact on bioavailability - Quevedo Olaya, Jhonsson Luis (2025)
The Peruvian diet is recognized worldwide for its diversity and exquisiteness, which has made it an international gastronomic benchmark. Proof of this is that Peru is home to some of the best restaurants in the world, with distinctions in prestigious guides such as The World's 50 Best Restaurants and Michelin stars. But this comes at a price, since its composition is dominated by foods rich in carbohydrates and processed, which negatively affects the health of the population. This study has set itself the challenge of analyzing how nutrients interact in the daily Peruvian diet and their effect on health. To this end, a literature review was carried out with studies published between 2014 and 2024, using academic databases and rigorous selection criteria. The results show that positive interactions, such as the combination of vitamin C with non-heme iron, improve the bioavailability of key nutrients, reducing problems such as anemia. However, the presence of phytates and tannins in the diet inhibits the absorption of essential minerals, which increases nutritional deficiencies in vulnerable populations. The study concludes by making a proposal for food combinations that improve nutrient absorption and modifying cooking methods can improve the nutritional quality of the Peruvian diet.